Making sense of baseline assessment - Sainsbury, Marian. (Hodder and Stoughton Educational, 1998)
Children starting school. What is baseline assessment for? Approaches to assessment. Planning teaching and learning. Understanding baseline scores. Measuring value added. Making baseline assessment work for you.